2005
DOI: 10.1111/j.1365-2788.2005.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Spanish adaptation and validation of the Family Quality of Life Survey

Abstract: The study provides a valid instrument for the research of the QOL of those families that have a child with a disability within Spanish-speaking community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
41
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 11 publications
9
41
0
5
Order By: Relevance
“…This questionnaire gives an overall score for QOL and the total score was used as the dependent variable in this study. The questionnaire was not previously applied in Croatia, but many cross-cultural studies have shown that the instrument is valid and reliable for use in various cultures (Verdugo, Córdoba & Gómez, 2005 ;Hu et al, 2011). Participants provide their answers on a 1-5 point Likert scale and rate their satisfaction with specific QOL aspects (1-not at all important, 5-very important).…”
Section: Instrumentsmentioning
confidence: 99%
“…This questionnaire gives an overall score for QOL and the total score was used as the dependent variable in this study. The questionnaire was not previously applied in Croatia, but many cross-cultural studies have shown that the instrument is valid and reliable for use in various cultures (Verdugo, Córdoba & Gómez, 2005 ;Hu et al, 2011). Participants provide their answers on a 1-5 point Likert scale and rate their satisfaction with specific QOL aspects (1-not at all important, 5-very important).…”
Section: Instrumentsmentioning
confidence: 99%
“…La ECVF (Beach Center, 2001) fue adaptada para la población colombiana (Verdugo, Córdoba & Gómez, 2005). La ECVF demostró un coefi ciente de estabilidad adecuado (r = 0.68 en Importancia y r = 0.78 en Satisfacción) y una excelente consistencia interna, el coefi ciente Alfa de Cronbach para Importancia fue de 0.96 y para Satisfacción fue de 0.95.…”
Section: Instrumentosunclassified
“…La muestra estuvo conformada por 158 familias. Se utilizaron dos instrumentos de recogida de información un Cuestionario Sociodemográfi co y la Escala de Calidad de Vida Familiar (Beach Center, 2001), ésta última adaptada previamente a población colombiana (Verdugo, Córdoba & Gómez, 2005, 2006. Los principales hallazgos demostraron que la calidad de vida de las familias está afectada por la falta de oportunidades para la inclusión social de personas adultas con DI/RM.…”
unclassified
See 1 more Smart Citation
“…En cuanto a la Satisfacción, los autores sostienen que, si bien se trata de un constructo menos estable, permite obtener información sobre el estado de cumplimiento de dichos aspectos que para la familia son relevantes en relación a la CV (Park et al, 2003). Se trata de una escala que ha sido validada en población española (Sainz & Verdugo, 2006) y colombiana (Verdugo, Córdoba, & Gómez, 2005) con lo cual se ha logrado extender el conocimiento respecto a la CVF fuera del contexto de los Estados Unidos.…”
unclassified